Ca2+ Microdomains in T-Lymphocytes - Wolf, Insa M. A.; Guse, Andreas H. (Frontiers in Oncology, 2017)
Early Ca2+ signaling is characterized by occurrence of Ca2+ microdomains formed by opening of single or clusters of Ca2+ channels, thereby initiating first signaling and subsequently activating global Ca2+ signaling mechanisms. However, only few data are available focusing on the first seconds and minutes of Ca2+ microdomain formation and related signaling pathways in activated T-lymphocytes. In this review, we condense current knowledge on Ca2+ microdomain formation in T-lymphocytes and early Ca2+ signalling, function of Ca2+ microdomains and microdomain organization. Interestingly, considering the first seconds of T cell activation, a triphasic Ca2+ signal is becoming apparent: (i) initial Ca2+ microdomains occurring in the first second of T cell activation, (ii) amplification of Ca2+ microdomains by recruitment of further channels occurring in the next 5-10 seconds, and (iii) a transition to global Ca2+ increase. Apparently, the second messenger NAADP is the first second messenger involved in initiation of Ca2+ microdomains. Ryanodine receptors type 1 act as initial Ca2+ release channels in CD4+ T-lymphocytes. Regarding the temporal correlation of Ca2+ microdomains with other molecular events of T cell activation, T cell receptor-dependent microdomain organization of signaling molecules Grb2 and SLP65 was observed within the first 20 s. In addition, fast cytoskeletal changes are initiated. Further, the involvement of additional Ca2+ channels and organelles, such as the Ca2+ buffering mitochondria are discussed. Future research developments will comprise analysis of the causal relation between these temporally coordinated signaling events. Taken together, high resolution Ca2+ imaging techniques applied to T cell activation in the past years paved the way to detailed molecular understanding of initial Ca2+ signaling mechanisms in non-excitable cells.